Kapasitas Penyerapan dan Penyimpanan Air pada Berbagai Ukuran Potongan Rumput Laut Sargassum sp sebagai Bahan Pupuk Organik - Haryza, Yuvita Christovora; Hastuti, Rini Budi (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2009)
Brown algae Sargassum sp is one species of seaweed that is existed in Indonesia. The species consist of kalium, macro and micro mineral, and gel with the existence of content, Sargassum sp can be managed as the organic fertilizer to increase the huminity of the fertilizer that is able to support the water absorbtion by the plant so that it can optimize the plant growth. This research possesses purpose to acknowledge the capacity amount of Sargassum sp toward the absorbtion and storage process of the water with the different slice measure that is 1 cm; 0,5cm; 0,25 cm. This research was held in the month of April – May 2006 in Laboratory of Structure Biology andPlant Function of MIPA Fakulty of Diponegoro University. The gained result from the research is the existence of the influence of the slice of Sargassum sp toward the absorbtion and storageprocess of water. The slice of 0,25 cm is the slice that possesses the biggest ability of the storage process of water whereas the slice of 0,5 cm is the slice that possesses the longest ability of the storage process of water.